Avaliação da arquitetura de copa da espécie Araucaria angustifolia (Bertol.) Kuntze com uso de geotecnologia na região central de Santa Catarina - Marasciulo, Alessandra Silva (2017)
The Araucaria angustifolia (Bertol.) Kuntze is currently an endangered species that has a big ecological importance on it's natural occurrance and is threatened with extinction. To recognize the factor that influence in the growth of this species is important to knowledge of the dynamics of your forests. The canopy architecture keeps informations about the trees and to study it's aspects and volume and other canopy variables helps to compreend the aspects that defines the shape of the canopy. The inserts of geotechnologies to the canopy study makes possible the understanding of the interactions and modifications of this structures, therefore being a fundamental instrument to interfere at the growth of the species and it's management. Considering this, this study had as objective to develop a model to describe the crown volume, using geotechnology, in function of dendrometrics, morphometrics and of competition variables to Araucaria augustifolia (Bertol.) Kuntze in Sistema Faxinal, Curitibanos, SC. To evaluation, 149 individual of Araucaria were submitted. 118 were in effect of competition and the variables of the treetops' architecture were taken to 78 Araucaria by digital images obtained of the utilization of geotechnology (RPA modelo Phantom 1) and measured by software AutoCAD. These indirect measurements showed good precision. 17 competition indexes were evaluated and Lorimer's index (1983) was selected to describe the best status of competition. The analysis of the tridimensional model of the canopy architecture showed that smaller trees has canopy shapes wider and flattened, and bigger trees has canopies extended and narrow. For the complete mathematical crown volume model as inserted as variables: DAP, H, IC2, RCM, LC, APC, AP, EST e SEXO. The construction of the canopy volume model, realized by the procedure Stepwise, contempled dendrometrics, DAP, morphometrics, crown length and cup profile area, and of competition, represented by Lorimer's competition index (1983). The model ajusted to the crown volume was VC=-27,6510+1,2629*(DAP)-28,6703*(IC2)-8,4328*(LC)+7,1848*(AP) and presented good statistics: R²aj = 0,8951 e Syx% = 7,77. The knowledge of the crown morphometrics characteristics allowed to interfere on the dynamics of growth of the trees when submitted to different conditions of it's environment.